Performance Theatre and the Poetics of Failure. - Bailes, Sara Jane (Taylor & Francis, 2010)
What does it mean to "fail" in performance, or more accurately, to stage failure in performance? What do performances that are founded upon the collapse of their own invention illuminate that other modes of theatre usually conceal? This book examines these questions through theoretical and archival modes of investigation.